2018
DOI: 10.24926/iip.v9i2.980
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a Longitudinal Reflection Curriculum: A Case Study Of Student Self-Awareness Expressed Through Rotation Goal Achievement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To increase self-reflection skill, Gilliam and colleagues have stressed that introducing in the first professional year a longitudinal reflective curriculum with strong emphasis on self-directed goal setting will result in greater achievement of the self-awareness domain over time. 17 Such a process was not in place, and heeding this advice, the IDEA structured self-reflection format is now included within our IPPE sequence as one step toward creating a longitudinal reflective pre-APPE curriculum. Additionally, King and colleagues found that while pharmacy students do find value in critical reflective writing, only 42% of students found critical reflection to have at least an appreciable or significant impact on professional development, posing the challenge of how to better engage students in the reflective process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase self-reflection skill, Gilliam and colleagues have stressed that introducing in the first professional year a longitudinal reflective curriculum with strong emphasis on self-directed goal setting will result in greater achievement of the self-awareness domain over time. 17 Such a process was not in place, and heeding this advice, the IDEA structured self-reflection format is now included within our IPPE sequence as one step toward creating a longitudinal reflective pre-APPE curriculum. Additionally, King and colleagues found that while pharmacy students do find value in critical reflective writing, only 42% of students found critical reflection to have at least an appreciable or significant impact on professional development, posing the challenge of how to better engage students in the reflective process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an assessment of interrater reliability within our evaluation process for our four EE faculty involved in the grading was lacking, which is a study limitation that may have slight impact on the rubric grading. To increase self‐reflection skill, Gilliam and colleagues have stressed that introducing in the first professional year a longitudinal reflective curriculum with strong emphasis on self‐directed goal setting will result in greater achievement of the self‐awareness domain over time 17 . Such a process was not in place, and heeding this advice, the IDEA structured self‐reflection format is now included within our IPPE sequence as one step toward creating a longitudinal reflective pre‐APPE curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…20 Stories are less than five minutes in duration and are told from memory without the aid of notes or prompts, a format similar to community-based storytelling events featured on The Moth Radio Hour and USA Today Network's Storytellers Project. 20,21 Story Slam serves as an introduction to the school's Reflective Practitioner Program, which engages students, individually and in peer groups, in mentored self-reflection through various modalities over the four-year curriculum. 22 As such, a formal assessment of student reflections presented during Story Slam is not conducted.…”
Section: Introductionmentioning
confidence: 99%